Climbing the Ladder of Equality: A Multifaceted Exploration of Feminist Ideals and Gender Dynamics in Shashi Deshpande’s Expansive Narrative Universe - Lovepreet Kaur; Dr Sushil Kansal (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This comprehensive study delves into the nuanced depiction of feminist themes and gender dynamics within the literary realm crafted by Shashi Deshpande. Through an in-depth analysis of Deshpande’s diverse narratives, this research elucidates the author’s exploration of feminist ideals and the quest for equality in various social contexts. By examining Deshpande’s portrayal of female characters and their experiences, this study unveils the complexities of gender relationships, societal expectations, and the struggle for autonomy and agency. Through a meticulous examination of Deshpande’s narrative techniques and thematic motifs, this research contributes to a deeper understanding of the feminist discourse in Deshpande’s oeuvre, shedding light on the transformative power of literature in challenging gender norms and advocating for women’s empowerment.